Resistance to black root - Davis, J.H.C.; Morales, Francisco José; Castaño, M. (1987)
Bean germplasm was evaluated at CIAT for resistance to BCMV strains NL-4, NL-3, and NL-5 in order to use them in the national breeding and selection programs in Africa, Europe, USA, and Chile. Ninety-eight lines were selected for an international Bean Common Mosaic/Black Root resistance nursery. Not all lines selected showed full resistance to black root but they all have genes that can be combined to obtain such resistance. (CIAT)